Wiedemann-Rautenstrauch neonatal progeroid syndrome: report of three new patients. Issue 5 (May 1997) - Arboleda, H; Quintero, L; Yunis, E
Abstract : Wiedemann-Rautenstrauch (WR) syndrome is known as a neonatal progeroid syndrome, with only few published case reports. We describe three additional patients, two of them sibs, showing the clinical features of WR syndrome. Skeletal abnormalities are reported and assays of hormones and lipids are presented in one patient. Disturbance in bone maturation and lipid and hormone metabolism appear to be involved in this neonatal progeroid syndrome.